Analisis Penentuan Suku Bunga Kredit Program Sektor Pertanian dan Potensi Pengaruhnya Terhadap APBN - Abdul Aziz, Sidiq Suryo Nugroho, Eko Wicaksono, dan (Jurnal Borneo Administrator, 2016)
This study is aimed to investigate the determination of interest rate subsidy provided by the government to help farmers and improve agricultural productivity. One parameter used to determine the interest rate of credit program is the Deposit Insurance Agency (LPS) interest rate. The basis for determining the interest rate credit program is one of the main issues discussed in this study. In addition, other matter discussed in this study is the proportion of interest expense borne each by the debtor and the government. The study is conducted by using mix methods analysis using primary data derived from the survey and secondary data related lending rates. Based on the analysis conducted, there are several conclusions that can be drawn. First, interest rates LPS is appropriate as the basis for determining the interest rate of credit interest rate guarantee program since LPS rate constitutes the largest portion of cost of fund.  Second, in the long term the government needs to evaluate patterns of current credit program so that it can both increase the selfreliance of farmers and improve the efficiency and efectivity of government subsidy. Third, for the time being the government can implement a fixed interest rate subsidy to credit the program with regard to the ability of farmers to minimize the fiscal risks exposure in the government budget.Keywords: Agriculture, credit program, subsidy, fiscal risk, fixed interest rate.Kajian ini bertujuan untuk melakukan analisis terhadap penetapan subsidi bunga kredit program yang diberikan oleh pemerintah untuk membantu petani dan meningkatkan produktivitas pertanian.Salah satu parameter dalam penentuan tingkat suku bunga kredit program adalah tingkat suku bunga penjaminan Lembaga Penjamin Simpanan(LPS).Dasar penentuan suku bunga kredit program merupakan salah satu permasalahan yang dibahas dalam kajian ini.Selain itu, hal lainnya yang dibahas dalam kajian ini adalah proporsi beban bunga yang ditanggung oleh debitur dan pemerintah.Kajian ini dilakukan dengan menggunakan metode campuran dengan menggunakan data primer yang berasal dari survei serta data sekunder terkait suku bunga kredit.Berdasarkan analisis yang dilakukan terdapat beberapa kesimpulan yang dapat diambil. Pertama, suku bunga penjaminan LPS layak untuk dijadikan dasar penentuan tingkat suku bunga kredit program karena suku bunga penjaminan LPS merupakan salah satu komponen terbesar biaya dana dari perbankan saat ini. Kedua, dalam jangka panjang pemerintah perlu untuk mengevaluasi pola pemberian kredit program saat ini sehingga di satu sisi dapat meningkatkan kemandirian petani dan disisi lain dapat meningkatkan efisiensi dan efektivitas belanja subsidi pemerintah. Ketiga, untuk saat ini pemerintah dapat menerapkan subsidi bunga tetap untuk kredit program dengan tetap memperhatikan kemampuan petani sehingga dapat meminimalkan risiko fiskal dalam APBN.Kata Kunci: Pertanian, kredit program, subsidi, risiko fiskal, suku bunga tetap.